Contamination of Microplastics in Retail Paratapes undulatus Clams from Fresh Markets in Nakhon Pathom Province, Thailand - Khamboonruang, Pattrawan; Rueawraengbunya, Mint; On Prommi, Taeng (Journal of Food Health and Bioenvironmental Science, 2023)
Microplastic contamination in food is a growing problem in the modern world. Clams, in particular, are consumed whole and are particularly susceptible to contamination entering the body. In 120 clams, microplastic contamination was investigated. Clam tissues were digested with 30% hydrogen peroxide and 10% potassium hydroxide. A total of 1,001 microplastic items were found. There was a statistically significant difference between the weights of clam tissue and microplastic (χ2 = 36.945, df = 5, p = 0.000; χ2 = 35.842, df = 5, p = 0.000). The most prevalent microplastic shapes, at 38% and 36%, were identified as fragment and film microplastics. The most common microplastic color was white or transparent (29%), whereas the majority (44%) of the microplastics were less than 100 µm. A Fourier transform infrared spectrometer (FTIR) was used to confirm 99 microplastics that were chosen at random and amounted to approximately 10% of the total microplastics. PET (polyethylene terephthalate), BEHP (bis(2-ethylhexyl) phthalate), PP (polypropylene), CA (cellulose acetate), PVAc (polyvinyl acetate), PMMA (poly (methyl methacrylate), and EC (ethyl cellulose) are examples of plastic materials. According to the study's findings, the Paratapes undulatus sold in Thailand's fresh market was heavily contaminated with microplastics. As a result, the findings of this study can be utilized to inform future research on assessing exposure to microplastics and the health risks associated with consuming contaminated bivalves commonly consumed in Thailand.